Comparison of Dexmedetomidine Versus Midazolam-Fentanyl Combination for Monitored Anesthesia Care During Burr-Hole Surgery for Chronic Subdural Hematoma. Issue 2 (April 2016) - Bishnoi, Vinod; Kumar, Bhupesh; Bhagat, Hemant; Salunke, Pravin; Bishnoi, Sonika
Abstract : Background: Intraoperative movements are marker of inadequate level of sedation and are undesirable during burr-hole surgery under monitored anesthesia care (MAC). It distracts surgeon, hinders surgical procedure, and may lead to iatrogenic complication. Dexmedetomidine has shown to provide excellent analgesia, cooperative sedation with fewer fluctuations in sedation level during MAC. We compared the effect of dexmedetomidine on intraoperative patient movement, postoperative recovery time, and the surgeon and patient satisfaction scores with commonly used midazolam-fentanyl combination. Methods: Fifty-two patients undergoing burr-hole surgery for chronic subdural hematoma under MAC were randomly assigned to receive either IV dexmedetomidine 1 μg/kg over 10 minutes followed by continuous infusion 0.03 to 0.07 μg/kg/h (group D) or IV fentanyl 0.5 μg/kg and midazolam 0.03 mg/kg over 10 minutes followed by continuous infusion of 0.5 to 1.16 μg/kg/h fentanyl and 0.03 to 0.07 mg/kg/h midazolam (group M/F) titrated to maintain Ramsay sedation scale 3. Total number of intraoperative patient movements, postoperative recovery time, and patient and surgeon satisfaction scores were recorded. Results: Demographic and baseline characteristics were comparable between the 2 groups. Intraoperative patient movements were significantly less in group D than group M/F (median interquartile range, 1.00 [0.00 to 2.00] vs. 3.00 [1.00 to 3.25], P =0.007). Group D patients showed faster postoperative recovery (mean±SD, 7.00±6.96 vs. 13.69±6.18 min, P =0.000). Surgeon satisfaction scores were better in group D compared with group M/F (median interquartile range, 1.00 [1.00 to 1.25] vs. 2.00 [1.00 to 2.00], P =0.014). However, patient satisfaction score and hemodynamic parameters were comparable ( P >0.05) between both the groups. Conclusions: Use of dexmedetomidine for MAC is associated with lesser number of intraoperative patient movements, faster postoperative recovery, better surgeon satisfaction score, and comparable patient's satisfaction compared with midazolam-fentanyl combination.